Report on professional attachment with Texas Instruments Singapore (Pte) Ltd. - Ting, Linda Hwee Hiang. (2009)
The main purpose of this report is to give an insight to the training experience gained by the student in Texas Instruments Singapore (Pte) Ltd under the Professional Attachment programme. This report will highlight the area of training the student has received in the Finance Department of TIS, the Subcontract Invoice Processing (SIP) project. Evaluation and comments by the student will be presented as the student describes the SIP project. Recommendation regarding SIP is given as well.